Presenting Innovative Solutions in Response to Variety-Seeking Behavior in Online Retail Customers - Soleimani, Ali; Aghajani, Mojtaba; Landaran, Saeid (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: Owners and managers of online retail stores, along with researchers, consistently strive to identify success factors in the online retail domain. One significant factor in the success of online retail stores is attention to consumer behavior. The aim of this research was to present innovative solutions for recognizing variety-seeking behavior in online retail customers. Methodology: This study was applied-descriptive and of the survey type. The research was conducted in two stages. Initially, innovation criteria were extracted from the literature, followed by an examination of the criteria’s impact intensity and the causal relationships between them using the DEMATEL technique and MATLAB software, with the tool of pairwise comparison matrices. Findings: The results of the study demonstrated that product innovation, service innovation, process innovation, innovation in online services, and innovation in tools play an effective role in the variety-seeking behavior of online retail customers. Furthermore, the results specified that product innovation, tools and equipment, processes, online services, and after-sales services have the most significant impact on the variety-seeking behavior of customers, in that order. Conclusion: Given the results of the study, it seems that the use of ideation, innovation, creativity in production, presentation, and sale in online retail is essential. In other words, it is necessary for manufacturers of goods and service providers to use new and innovative ideas in the production and presentation of goods and services to be an appropriate response to the needs and variety-seeking behavior of customers.